Immunological Abnormalities In PCOS - Barcińska, Joanna Maria; Ostrowska-Czyżewska, Aleksandra; Szwed, Dominika (Quality in Sport, 2024)
PCOS (Polycystic Ovary Syndrome) is a condition associated with irregular ovulation, hyperandrogenism and metabolic disturbances. It affects 10-15% of reproductive ages and it is a common reason for infertility. The basis of PCOS is chronic low-grade inflammation, which is expressed by an increase in inflammatory biomarkers such as CRP, IL6, IFN gamma, TNF alpha, IL10, 17,18 MCP-1 and an increase in the percentage of lymphocytes especially Th1 and macrophages, eosinophils compared to the healthy population. The hormonal imbalances in PCOS may contribute to dysregulation of the immune system, leading to the production of a diverse range of autoantibodies for a spectrum of systemic connective tissue diseases, lupus erythematosus, scleroderma, dermatomyositis, polymyositis, and Sjögren's syndrome. This article reviews the results of previous research on this topic. It was prepared to summarize the latest knowledge about immunological abnormalities in PCOS and to define new therapeutic drug action points.